8.3: Blur‐Free Transparent LCD with Hybrid Transparency. Issue 1 (1st July 2013) - Kuo, Chia‐Wei; Lin, Ching‐Huan; Liao, Yi‐Yang; Lai, Yi‐Hsiang; Chuang, Chin‐Tang; Yeh, Cheng‐Nan; Lu, Jen‐Kuei; Sugiura, Norio
Abstract In this paper, a 65‐inch blur‐free transparent LCD was presented. A simple way of controlling LC orientation was applied to suppress the issue of blurry images behind transparent LCD. Furthermore, the individual controllable RGBW sub‐pixels were used to improve the transmittance and realize the hybrid transparency on the display.